HIGH-TECH MEDICAL CARE TO RESTORE BLOOD FLOW IN PATIENTS WITH RESTENOSIS (European Journal of Interdisciplinary Research and Development, 2023)
Over the past 10-15 years, we have distinguished ourselves by the economically rapid growth and development of many countries of the world. This fact leads to significant changes in both living conditions and significantly improves the quality of life. In turn, adherence to an unhealthy lifestyle, in particular to an unhealthy diet; a high rate of arterial hypertension; a hypodynamic lifestyle, smoking and all sorts of other risk factors; which provoked the occurrence of atherosclerotic changes. These include atherosclerosis of the cardiovascular system (CFS), which defined coronary heart disease (CHD) as the leader in the level of death and disability in the countries of the world [1,3-6]. Its universal prevalence of percutaneous intervention (PCI), including the CV stenting method, in the therapeutic approach of various forms of coronary heart disease has led to a progressive increase in the number of restenoses, which is currently the most burdensome problem of interventional cardiology [2,4]. Reliable determination of the frequency of restenosis after PCI is not such an easy task. Various sources state that during the period before the creation of coronary stents, following balloon angioplasty, the frequency of restenosis reaches 35-57%.